Barriers to utilization of pre-hospital emergency medical services among residents in Libreville, Gabon: A qualitative study - Bosson, Nichole; Redlener, Michael A.; Foltin, George L.; Raven, Maria C.; Foran, Mark P; Wall, Stephen P. (African Journal of Emergency Medicine, 2013)
In 2002, the West-African nation of Gabon established an emergency medical system (EMS), Service d’Aide Médicale Urgente (SAMU), in Libreville, yet few people access it. Our objective was to describe Libreville residents’ knowledge and attitudes toward the SAMU in an effort to understand why this service is underutilized. Qualitative interviews consisting of nine open-ended questions were conducted on a convenience sample of twenty patients, three visitors and two patient/visitor dyads at the Jeanne Ebori Hospital Emergency Centre in October 2009. Eligible subjects arrived in vehicles other than the SAMU and were ill enough to require hospital admission. Exclusion criteria were: under 21years old, unable to speak French, or medically unstable. A bilingual team member audio-recorded the interviews in French and transcribed them into English. Investigators organized text into codes, then into themes and theoretical constructs. Intercoder agreement was excellent. Data were collected until theoretical saturation was achieved. Analysis of data revealed no difference in response between patients and visitors. People underused SAMU because of financial costs, lack of awareness of the program, use of traditional modes of transportation, infrastructure flaws, perceived response times and other misconceptions. We identified remediable barriers to EMS (SAMU) access in Libreville, Gabon: lack of awareness, misperceptions, established alternatives, and cost. Interventions and future investigations designed to increase EMS utilization in Gabon should target these four areas. En 2002, ce pays d’Afrique de l’Ouest qu’est le Gabon a mis en place un Service d’Aide Médicale Urgente (SAMU) à Libreville, mais peu de personnes y ont recours. Notre objectif était de décrire les connaissances des habitants de Libreville et leurs attitudes vis-à-vis du SAMU afin de comprendre pourquoi ce service reste sous-utilisé. Des entretiens qualitatifs comportant neuf questions ouvertes ont été réalisés auprès d’un échantillon de convenance de vingt patients, trois visiteurs et deux couples patient/visiteur du service d’urgence de l’hôpital Jeanne Ebori en 2009. Les sujets éligibles sont arrivés dans des véhicules autres que ceux du SAMU et étaient suffisamment malades pour être hospitalisés. Les critères d’exclusion étaient les suivants : moins de 21 ans, non francophone ou médicalement instable. Un membre bilingue de l’équipe a fait un enregistrement audio des entretiens en français et les a retranscrit en anglais. Les enquêteurs ont codé le texte, puis en ont dégagé des thèmes et des interprétations théoriques. La cohérence entre les codeurs était excellente. Des données ont été collectées jusqu’à saturation théorique. L’analyse des données n’a révélé aucune différence dans les réponses entre patients et visiteurs. Les personnes sous-utilisent le SAMU pour des raisons financières, par manque de sensibilisation au programme, parce qu’elles utilisent des moyens de transport traditionnels, à cause des infrastructures inadaptées, parce que le SAMU est perçu comme un service lent et autres idées reçues. Nous avons identifié des obstacles à surmonter pour l’accès au SAMU à Libreville, au Gabon : un manque de sensibilisation au service, une perception erronée de celui-ci, des alternatives à ce service et son coût. Les interventions et les futures enquêtes destinées à accroître l’utilisation du SAMU devront cibler ces quatre domaines.